BREAST MILK IN ALL ASPECTS - Emine Gülbin Gökçay; Elmas Zeynep İnce; Gonca Keskindemirci; Asuman Gedikbaşı; Yeliz Güven; Şerif Emre Gökçay; Fatoş İlkay Alp Yıldırım; Sema Bayraktar (İstanbul Tıp Fakültesi Dergisi)
Exclusive breastfeeding for the first six months and continuing to breastfeed until at least 2 years of age is recommended by the Ministries of Health of countries worldwide. Breastfeeding contributes to health not only through its nutritional but also im munological properties. Breast milk has unique ingredients that ensure healthy growth. It is rich in bioactive substances such as growth factors; cytokines, microRNAs, human milk oligosaccha rides, and cells. Epigenetic studies have identified differences in gene expression between breastfed and formula-fed infants. DNA methylation (DNAm) has been suggested as a mechanism under lying the long-term health effects of breastfeeding. Breastfeeding promotes proper maxillofacial growth and development by stimu lating intense oral muscular activity, promoting correct lip closure, mandibular function, and tongue positioning on the palate. In economics, merit good is generally accepted as good (product) that societies should consume regardless of individuals’ wishes or demands. The most typical examples of merit products are education and health. From an economic perspective, it can be concluded that breast milk is an economically merit product, and the states should allocate resources by using their public power to increase breastfeeding. Pharmacists and nurses play important and crucial roles in supporting and assisting mothers during the breastfeeding period. Nurses should always play an active role in initiating and maintaining breastfeeding at every stage of life. In this review, breast milk is discussed in every aspect.